Granulocyte colony-stimulating factor protects against acute systemic alphavirus disease in a type I IFN-dependent manner - Hameed, Muddassar; Rai, Pallavi; Hossain, Md Shakhawat; Daamen, Andrea; Lipsky, Peter E.; Weger-Lucarelli, James (Frontiers in Immunology, 2025)
IntroductionArthritogenic alphaviruses, including chikungunya (CHIKV) and Mayaro virus (MAYV), cause disease characterized by fever, rash, and incapacitating joint pain. Alphavirus arthritis is associated with infiltration of myeloid cells and increases in several cytokines systemically, including granulocyte colony-stimulating factor (G-CSF). G-CSF is secreted by endothelial cells, fibroblasts, macrophages, and monocytes and binds to colony-stimulating factor 3 receptor (CSF3R, also known as G-CSFR) on the surface of myeloid cells. G-CSFR signaling initiates the proliferation, differentiation, and maturation of myeloid cells, especially neutrophils. Importantly, G-CSF has been found at high levels in both the acute and chronic phases of chikungunya disease; however, the role of G-CSF in arthritogenic alphavirus disease remains unexplored.MethodsHere, we sought to test the effect of G-CSF on CHIKV and MAYV infection using G-CSFR-deficient mice (G-CSFR-/-).ResultsCompared to wild-type mice, we observed sustained weight loss in G-CSFR-/- mice following CHIKV and MAYV infection. Furthermore, G-CSFR-/- mice had a significantly higher percentage of inflammatory monocytes and a reduction in neutrophils throughout infection. The difference in weight loss in G-CSFR-/- mice induced by alphavirus infection was corrected by blocking type I IFN signaling.DiscussionIn summary, these studies suggest that type I IFN signaling contributes to G-CSFR-mediated control of arthritogenic alphavirus disease. Therefore, G-CSF or G-CSFR may be therapeutic targets to modulate host immune responses against arthritogenic alphavirus disease.